Effects of hypercapnic hyperpnea on recovery from isoflurane or sevoflurane anesthesia in horses - Brosnan, Robert J.; Steffey, Eugene P.; Escobar, André [UNESP] (Wiley-Blackwell, 2012)
Objective To test the hypothesis that hypercapnic hyperpnea produced using endotracheal insufflation with 5-10% CO2 in oxygen could be used to shorten anesthetic recovery time in horses, and that recovery from sevoflurane would be faster than from isoflurane.Study design Randomized crossover study design.Animals Eight healthy adult horses.Methods After 2 hours' administration of constant 1.2 times MAC isoflurane or sevoflurane, horses were disconnected from the anesthetic circuit and administered 0, 5, or 10% CO2 in balance O-2 via endotracheal tube insufflation. End-tidal gas samples were collected to measure anesthetic washout kinetics, and arterial and venous blood samples were collected to measure respiratory gas partial pressures. Horses recovered in padded stalls without assistance, and each recovery was videotaped and evaluated by reviewers who were blinded to the anesthetic agent and insufflation treatment used.Results Compared to isoflurane, sevoflurane caused greater hypoventilation and was associated with longer times until standing recovery. CO2 insufflation significantly decreased anesthetic recovery time compared to insufflation with O-2 alone without significantly increasing PaCO2. Pharmacokinetic parameters during recovery from isoflurane with CO2 insufflation were statistically indistinguishable from sevoflurane recovery without CO2. Neither anesthetic agent nor insufflation treatment affected recovery quality from anesthesia.Conclusions and clinical relevance Hypercapnic hyperpnea decreases time to standing without influencing anesthetic recovery quality. Although the lower blood gas solubility of sevoflurane should favor a shorter recovery time compared to isoflurane, this advantage is negated by the greater respiratory depression from sevoflurane in horses.
Keywords: carbon dioxide; Horse; Hypercapnia; Isoflurane; recovery; Sevoflurane